The impact of extremely high levels of PM2.5 on surface ozone during massive dust storms - Amin Nawahda (Kuwait Journal of Science)
Large amounts of Particulate Matter (PM) produced by dust storms can have adverse effects on health. When inhaled, PM2.5 (PM having a diameter of 2.5 ​μm or smaller) can cause serious respiratory problems in young children and the elderly. Despite of these adverse impacts dust storms can help remove gaseous pollutants through dry deposition. Thus, the aim of this study is to show the temporal variation of the monitored PM2.5 and to identify its effect on ozone (O3) during dust storms. In 2015 massive dust storms blowing from southern deserts in Iran and Saudi Arabia hit many areas in the Gulf region including the Sultanate of Oman. In the Sohar region these storms were the biggest in over a decade and caused extremely high levels of PM2.5 that exceeded 350 ​μgm−3 and reached up to 1884 ​μgm−3. Impressively it was found that dust storms reduced the concentrations of the precursors of surface ozone (NO, NO2, NOx); (correlation coefficients; −0.53, −0.69, and −0.67, respectively). Accordingly, for air quality management, in areas with similar and frequent conditions, international air quality guidelines and standards from both World Health Organization (WHO) and the U.S. Environmental Protection Agency (USEPA) are inappropriate. Thus, in Arabian Gulf countries, where people spend more time indoors, it is necessary to set national guidelines for managing air quality by considering local environmental conditions.